(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Urban analysis as a scientific method can be applied to both modern cities and historical cities. Most of the monuments in the historic towns and villages consist of several ancient buildings. Most of these buildings are examples of folk architecture and majestic architecture. Ancient engineering structures such as bridges, dams and wells are also among the architectural monuments.